Reproductive indices in malaria infested mice treated with antimalarials, Phyllanthus amarus combined with vitamins - Matthew Obaineh Ojezele; Ighodaro Igbe; Agbonlahor Okhuarobo (Faculty of Pharmacy, Cairo University, 2018)
Malaria disease is caused by the plasmodium organism transmitted into humans by the female anopheles mosquito. The effect of chloroquine, artesunate or Phyllantus amarus alone or combined with vitamins A, B, C or K on male fertility indices has received no attention. Hence this study was designed to investigate the effect of chloroquine, artesunate or seed extract of Phyllanthus amarus with or without vitamins A, B, C or E on testosterone levels, sperm motility, morphology, viability and count in mice infected with Plasmodium berghei. Four days following inoculation of adult male mice with Plasmodium berghei, the mice were treated with artesunate, chloroquine or Phyllanthus amarus seed extract alone or in combination with vitamins A, B, C or E once daily. Thereafter the mice were sacrificed and semen was collected for the determination of sperm count, motility, morphology and viability and blood sample collected for the determination of serum testosterone level by standardized methods. Treatment with chloroquine, artesunate or Phyllanthus amarus seed extract with or without vitamins A, B, C or E caused a significant (p < 0.05) increase in serum and semen testosterone levels in Plasmodium berghei infected mice. Treatment with chloroquine, artesunate or Phyllanthus amarus seed extract also caused a significant (p < 0.05) increase in sperm count, motility and viability as well as significant (p < 0.05) restoration of sperm morphology in Plasmodium berghei infected mice compared to untreated Plasmodium berghei infected mice. Results from our study suggest that vitamin supplement with antimalarial could enhance reproductive indices. Keywords: Phyllanthus amarus, Chloroquine, Artesunate, Plasmodium berghei testosterone, Sperm